The Role of Islamic Education in Countering Radicalism and Extremism: A Literature Review - Abdullah Sahin (PT. Berkah Smart Academica, 2025)
The infiltration of radical ideology and religious extremism within digital educational environments has become a formidable threat to social integration and the cognitive stability of the younger generation. This study aims to analyze the strategic role of Islamic Religious Education (IRE) in mitigating radicalism by evaluating the effectiveness of contemporary curricula and pedagogical strategies. The methodology employed is a Systematic Literature Review (SLR) utilizing the PRISMA protocol, which screened 120 articles to yield 25 core reputable peer-reviewed papers (2021-2025) as primary data. Data analysis was conducted using the content analysis technique to identify the most effective patterns of educational intervention. The findings indicate that the transformation of IRE from an indoctrinative model toward a dialogical-inclusive model based on Wasathiyyah (moderation) values constitutes the most dominant counter-extremism instrument. These results confirm that the integration of digital religious literacy into the IRE curriculum enhances students' resilience against extremist narratives in cyberspace. In conclusion, IRE serves as a primary ideological defense that deconstructs absolute truth claims through the strengthening of critical reasoning and universal empathy. This research recommends the standardization of a religious moderation curriculum that is adaptive to digital dynamics to ensure the continuity of harmony within a multicultural society.